Suitability Analysis between Expectations and Reality of Employee from Organizational Aspect at Bulu Lor Public Health Center in Semarang - Rizqi Amanullah; - Sudiro; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
Background; At the health center Bulu Lor Semarang was obtained employees dissatisfaction to leadership, compensation, work environment, promotion opportunities, and supervision. The purpose of this study was to determine the fit between the expectations and reality of employee’s job satisfaction in the organizational aspects of the health center Bulu Lor Semarang. Method; This research is an observational method and cross sectional survey. The research aspects were leadership, compensation, work environment, promotion opportunities, and supervision. The sample was civil servant who works in the health center of Bulu Lor Semarang totaling 17 people. The instrument in this study was using questionnaire that given twice, the first are expectations and the second are reality. Analysis of the research data was using Importance- Performance Analysis by Cartesian Diagram. Result; The results showed the level of suitability between expectation and reality employees are leadership 89.95%, compensation 82.82%, work environment 76,47%, promotion opportunities 86.59%, and supervision 84.50%. Summary of Cartesian diagram analysis shows that work environment needs to be fixed and there are aspects to maintain; compensation and leadership. Conclusions; It can be concluded that characteristics of the respondents in the health center of Semarang Bulu Lor percentage are, 58.8% Early Adult (26-35 years), 82.4% female, 82.4% are highly educated (D3, D4, S1), 76.5% period the new work is less than 10 years, and each as much as 17.6% holding positions as doctors, Sanitarian, Nurse, Administrative staff, The level of suitability between expectation and reality employees are leadership 89.95%, compensation 82.82%, work environment 76,47%, promotion opportunities 86.59%, and supervision 84.50%. Summary of Cartesian diagram analysis shows that work environment needs to be fixed and aspects to maintain are compensation and leadership